The Influence of the Role of Parents Through Self-Regulation on the Learning Interest of Elementary School Students - Syahadhata, Eling; Handoyo, Eko; Yusuf, Amin (Journal of Primary Education, 2021)
Self-regulation in elementary school children is very necessary because at this age children often impose their will (desire) by demonstrating the ability to choose, perform and decide something yourself. If the child is familiar with the rules, the child will feel safer, because the child knows which actions are allowed and which are not. The purpose of this study was to examine the effect of parental roles on students' interest in learning and to test how much self-regulation moderates the influence of parental roles on students' interest in learning. This study used a quantitative method. The sample in this study were 65 students from the Raden Said cluster in Kajar Village, Dawe District, Kudus Regency. The results of this study are (1) The role of parents towards their children in learning is quite good. The results of statistical tests obtained p-value of 0.020 (<0.05). It can be concluded that the role of parents has an influence on students' interest in learning; and (2) Self-regulation moderates the effect of the role of parents on students' interest in learning as indicated by changes in the r-square value, where in the first test without involving self-regulation, it is obtained 0.482 or 48.2%, while the r-square value in the second test rose to 0.570 or 57%. The conclusion from the results of this study is that the role of parents is quite good by providing support for children, paying attention to school assignments and lessons, providing additional tutoring outside of school, and shown in parental involvement in school activities.